Involvement of the Ubiquitin-Proteasome System in the Formation of Experimental Postsurgical Peritoneal Adhesions - Clara Di Filippo; Pasquale Petronella; Fulvio Freda; Marco Scorzelli; Marco Ferretti; Sivestro Canonico; Francesco Rossi; Michele D'Amico (Mediators of Inflammation)
We investigated the Ubiquitin-Proteasome System (UPS), major nonlysosomal intracellular protein degradation system, in the genesis of experimental postsurgical peritoneal adhesions. We assayed the levels of UPS within the adhered tissue along with the development of peritoneal adhesions and used the specific UPS inhibitor bortezomib in order to assess the effect of the UPS blockade on the peritoneal adhesions. We found a number of severe postsurgical peritoneal adhesions at day 5 after surgery increasing until day 10. In the adhered tissue an increased values of ubiquitin and the 20S proteasome subunit, NFkB, IL-6, TNF-α and decreased values of IkB-beta were found. In contrast, bortezomib-treated rats showed a decreased number of peritoneal adhesions, decreased values of ubiquitin and the 20S proteasome, NFkB, IL-6, TNF-α, and increased levels of IkB-beta in the adhered peritoneal tissue. The UPS system, therefore, is primarily involved in the formation of post-surgical peritoneal adhesions in rats.